Steel fibres as flexural cracks inhibitor in reinforced fibrous concrete beams under static loading / Mohd Yuasrizam Musa - Musa, Mohd Yuasrizam (2015)
Flexural cracks are the most common problem in structural members which are subjected to bending moments. The introduction of steel fibres in concrete beam has been proposed as flexural cracks inhibitor. This research of steel fibres as flexural cracks inhibitor in concrete beam under static loading was conducted focusing on simply supported beam to determine the crack propagations in flexure by varying the steel fibre content placement in the beam. The 25 kg/m3 steel fibre was chosen for this study since the optimum concrete strength (fcu) is achieved with this steel fibre dosage. Seven sets of concrete beams of 150 mm x 250 mm x 1000 mm in size consists of three RC beams with full steel fibrous concrete (SFRC), three RC beams with steel fibre placed within tension zone of the beam, three RC beams with steel fibre placed at the half o f tension zone of the beam, two conventional RC beams (without steel fibre) as control sample, one unreinforced concrete beam with full steel fibre, one unreinforced concrete beam with steel fibre at tension zone only and one unreinforced concrete beam with steel fibre at half of tension zone. The variations in these seven sets of beams is intended to find the optimum steel fibrous concrete placements towards inhibiting flexural cracks in the beam. Experiment was conducted through three points bending test. The results showed that addition of steel fibre in conventional reinforced concrete beam increase the crack initiation load, yield load and ultimate load by 60%, 69% and 56% respectively. It also reduced the ratio of ultimate load over yield load by 46% and increased the ratio of ultimate load over theoretical load by 40%. The crack opening is reduced by 11 %. The crack failure of all the beams are classified as flexure crack and occurred in the mid third span. The addition of steel fibre in the conventional RC beam showed that it inhibits the flexural cracks.